Promoting Women's Participation in Cross-border Trade in South Asia. Issue 1 (June 2019) - Livani, Talajeh; Solotaroff, Jennifer
Historically, practitioners and policymakers have overlooked gender issues in the trade space; however, research in recent decades strongly suggests that trade is not gender neutral. Cross-border trade produces changes in employment and prices, and these changes have different effects on women and men. Moreover, because women and men do not have equal access to education, networks, transportation and productive resources, their ability to seize trade-related opportunities differs. General trade barriers, such as deficient infrastructure and cumbersome regulatory and documentary requirements, also have gender-differentiated impacts. Drawing from the global literature, this article proposes policy recommendations to expand the benefits of trade to women in South Asia. The recommendations range from strengthening female-dominated export sectors and implementing trade facilitation measures to increasing women's access to training, productive resources, information, transportation and trade networks.